Numerical modeling the impacts of increasing groundwater pumping upon discharge decline of the BL Spring located in Xilin Gol League in east inner Mongolia, China - Xiao, Han; Yang, Yu; Liu, Qiyuan; Zang, Yongge; Lian, Xinying; Xia, Fu; Jiang, Yonghai (Frontiers in Environmental Science, 2024)
Spring discharge decline induced by increasing groundwater pumping under the background of increasing water demand for agricultural, industrial, and domestic utilizations has been recognized as a significant geo-environmental issue which poses a great threat to springshed eco-environmental safety. In this study, numerical approach was utilized and a series of 3D groundwater flow models based on the MODFLOW module were developed to simulate current-stage and future trends of spring discharges under the impacts of increasing groundwater pumping due to the rapid development of tourism in the BL spring located in Xilin Gol League in east Inner Mongolia (China), for the purpose of understanding the responses of spring discharges to various groundwater pumping scenarios in future. Simulation results indicated that: (1) spring discharge has reduced from 201.4 m3/d to 193.7 m3/d (reduction ratio of 3.80%) under current-stage pumping scheme; (2) the spring-discharge-affected zone is 2.025 km2 under current-stage pumping scheme and groundwater pumping within this zone contributes to spring discharge decline; (3) impact of the pumping well located nearest to the BL spring is the most significant while impact of the pumping well located farthest to the BL spring is negligible; and (4) spring discharge would reduce 25%, 50%, 75%, and 100% if total pumping rate of the seven abstraction wells would increase from 45.8 m3/d (current-stage pumping scheme) to 297.7, 586.2, 888.5, and 1,176 m3/d, respectively. The outcome of this study can provide useful references for advising sustainable groundwater exploitation strategies to meet the requirement of groundwater supply under the premise of spring discharge management and eco-environmental protection.